O surdo e o mercado de trabalho na cidade de Manaus - (:unkn) unknown (Universidade Federal do Amazonas, 2006)
The capitalist society is competitive and extremely exculpatory and the requirements for the access to the work market come increasing since the new social organization of the work establishes new parameters of ingression in the market and, in this perspective, the ability and the qualification are recurrent concepts in the world of the work and the world of the school. For the deaf person, who is a minority, the situation becomes more difficult, therefore this if comes across with innumerable barriers that make it difficult its insertion in the work market. Amongst the impediments we can elucidate: low level of education, absence of a linguistic environment, incipient professional formation, vision of the society in a perspective of the deficiency. The advances in relation to the process of social inclusion of the people with necessities special, in the area of the work if materialize with the Decree Nº 3,298/1999 that it regulates Law 7,853/1989, that shows: The Company with one hundred or more used is obliged to fill of 2% 5% of its rehabilitated beneficiary positions of the Social welfare or with person with deficiency. Although this, we evidence that the offered conditions are minimum. In this paper we analyze the process of inclusion of the deaf person in the market of work in the electro-electronic sector of the Zona Franca of Manaus and the barriers faced for the access to the work; To identify the main difficulties found for the deaf person for its insertion in the work market; to identify the main functions and busy positions for the deaf people in the companies; To analyze the politics of job of the companies for insertion of the deaf person in the work market, inside of the proposal of social inclusion; To verify which the requirements of qualification of the deaf person for the work market. The data had been collected by means of half-structure interview in 2 (two) plants of the Industrial District, specifically in the sector of human resources and with 15 diligent deaf people of the respective companies. The data indicates that the low level of education is one of the factors that difficult the access to the work market, since the minimum of education demanded for the companies is high school level. Looking through the law is evidenced it precariousness in its implementation. It was verified that the busy positions are in the sector of production and assembly. The access of the deaf person in the work market is a reality marked for the exclusion, considering that a preparation in the companies for the accessibility of these people does not exist, as the presence of an interpreter in courses or lectures. In synthesis practical the social ones are marked by the preconception and discrimination.
Keywords: Surdez; Educação; Inserção no mercado de trabalho; Inclusão; Exclusão; Surdez; Educação; Inserção no mercado de trabalho; Inclusão; Exclusão; Deafness; Education; Insertion in the work market; Inclusion; Exclusion; CIÊNCIAS HUMANAS: EDUCAÇÃO